THE INFLUENCE OF RESOURCE MANAGEMENT ON LEARNING STRATEGIES AMONG UNDERGRADUATES - Hj. Zaiton, Siti Nurul ‘ain; Borhanuddin, Rahayu Izwani; Shah, Nurisya Mohd; Asli, Milla-Armilla; Rahmat, Noor Hanim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study examines how undergraduate students use learning strategies with a particular focus on resource management, cognitive, and metacognitive techniques. It explores students’ perceptions of these strategies and their impact on learning. The study employs a quantitative survey methodology using a 5-point Likert scale instrument consisting of 41 items across four sections. Data were collected from 318 undergraduate students. The results were analyzed with SPSS to present findings that address the research questions of this study. The findings indicate that students’ cognitive strategies focus on memorization and organization of information, prioritizing mental and written methods instead of verbal or visual approaches. Although they practice critical thinking, their approach focuses more on linking new information to prior knowledge and assessing validity, rather than generating original concepts or thoroughly examining evidence. Students perceive their metacognitive strategies as a means of actively monitoring and regulating comprehension, mainly by recognizing and addressing points of confusion. They effectively apply self-monitoring and adaptive learning strategies but are less inclined to engage proactively in pre-reading strategies, such as formulating questions. The minimal in-class distractions indicate that they see themselves as attentive learners. The results also suggest that students manage their learning effectively by controlling their environment and effort, demonstrating resilience and a strong degree of persistence, even when facing challenging or less engaging content. They actively seek assistance, mainly from peers, when they face challenges. Although they typically handle their study environment effectively, there is a small inconsistency in completing all weekly tasks. The findings indicate a notable connection between resource management and their cognitive approaches, as well as metacognitive regulation. This suggests that efficient resource management is a crucial element related to a learner’s application of both fundamental study methods and advanced self-regulation skills.